Translation and content validity of the Dutch Impact of Vision Impairment questionnaire assessed by Three-Step Test-Interviewing - T. P. Rausch - Koster; A. J. van der Ham; C. B. Terwee; F. D. Verbraak; G. H. M. B. van Rens; R. M. A. van Nispen (SpringerOpen, 2021)
Abstract Background Patients suffering from exsudative retinal diseases may experience severe central vision loss and this might have impact on their daily activities and quality of life. To measure the disabilities these patients may have, the use of the Impact of Vision Impairment Profile questionnaire is recommended. The aim of this study was to translate the original English 28-item Impact of Vision Impairment Profile (IVI) into the Dutch language and evaluate its comprehensibility, comprehensiveness and relevance as evidence of content validity. The translation process was performed using standardized methods. Content validity was assessed by cognitive debriefing using a Three-Step Test-Interview (TSTI) method for participants diagnosed with exudative retinal diseases. Step 1 and 2 focused on assessment of comprehensibility of items, step 3 on comprehensiveness and relevance. Audio-recorded qualitative data was analyzed using Atlas.ti. Data regarding comprehensibility problems was further categorized into item-specific problems and general problems. Results Few minor discrepancies in wording were found after translation. After conducting 12 cognitive interviews, data saturation was reached. All participants reported comprehensibility problems resulting from specific items, these were; sentence structure, vocabulary and formulation, influence of conditions or composite items and influence of comorbid disorders. Several general comprehensibility problems resulting from instructions or response categories were detected. The main general comprehensibility problem resulted from the layout of the Dutch-IVI. Most participants considered the included items as relevant and indicated that they covered the problems that occur due to vision impairment. Conclusions Minor problems in the Dutch translation were detected and adjusted. The layout and instructions of the Dutch-IVI resulted in some comprehensibility problems. The Dutch-IVI appeared to be at risk of being interpreted as a generic patient reported outcome measure, instead of a disease-specific instrument, mainly due to the influence of co-morbidities. Adaptations should improve validity and reliability of the Dutch-IVI, however, cross-cultural comparisons may be at stake.